PENINGKATAN KEMAMPUAN MENULIS PESERTA DIDIK DISGRAFIA MENGGUNAKAN APLIKASI MARBEL MENULIS DI SDN SULUK 03 MADIUN - Marthadiputri, Febri Tri; Mochamad Nursalim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Children with learning difficulties in writing (Dysgraphia) are one of the 'Learning Disorders'. In children with Dysgraphia, the process of writing information is very difficult. Children with Dysgraphia can improve their writing skills by continuously doing writing activities using appropriate and interesting media. The research was conducted at SDN Suluk 03 with subjects of 7 male students, 3 female students. In the study, the author chose assistive media, the Marbel writing application which was developed in learning. The purpose of the study was to increase the motivation and writing skills of children with dysgraphia. The method used in the study was quasi-experimental with a pre-test and post-test approach to measure changes in students' writing skills and learning interests before and after using the Marbel Writing application. For data collection techniques using observation, documents and interviews with the help of questionnaires. Based on the recapitulation of responses, children with dysgraphia got 80% or were categorized as children with dysgraphia really like it and there were changes in writing skills and sentences. Thus, the Marbel Writing application can be applied in writing learning for children with dysgraphia.